Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
Rigidities in Greece's product and labor markets leading to economic imbalances and the significance of reforms to these markets are played out in the first paper. The second paper describes the problems, progress to date, and agenda for work in Greece's revenue administration and how this effort has been achieved primarily by raising tax rates to high levels and reducing wages, pensions, and other spending. The third paper is on the need for designing and implementing debt restructuring frameworks as well as improving banks' loan resolution practices so that Greece's banks are positioned to support the economic recovery.